Trends in Commuting Time of European Workers: A Cross-Country Analysis - J. Ignacio Gimenez-Nadal; José Alberto Molina; Jorge Velilla (Institute of Labor Economics (IZA), 2020)
This paper examines the time spent commuting to/from work by workers in fifteen European countries, during the last three decades, with the aim of analyzing recent trends in commuting and the factors affecting commuting behavior in those countries. Using data from several waves of the European Working Conditions Survey, results show a significant gender gap in commuting time in Austria, Belgium, France, Germany, Italy, Ireland, Luxembourg, the Netherlands, and the UK, with male workers devoting more time to commuting than their female counterparts. We further explore the factors related to commuting time, documenting a level of heterogeneity in commuting behavior as certain determinants of commuting time differ across countries. By analyzing the evolution of commuting time in Europe in recent decades, and the factors associated with commuting time, our analysis may serve to guide future planning programs.
Keywords: R40; O57; 330; commuting time; european working conditions survey; trends; gender; socio-demographic factors